2009
DOI: 10.1186/1471-2199-10-75
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of urokinase plasminogen activator receptor variants in human airway and peripheral cells

Abstract: Background: Expression of the urokinase plasminogen activator receptor (UPAR) has been shown to have clinical relevance in various cancers. We have recently identified UPAR as an asthma susceptibility gene and there is evidence to suggest that uPAR may be upregulated in lung diseases such as COPD and asthma. uPAR is a key receptor involved in the formation of the serine protease plasmin by interacting with uPA and has been implicated in many physiological processes including proliferation and migration. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 43 publications
1
43
1
Order By: Relevance
“…In conclusion, although several uPAR mRNA splice variants have been described, some being clearly associated to disease [14][15][16], no experimental analysis of their cellular properties was reported so far. The present study, combining in vitro and in vivo experimental approaches, clearly demonstrates tumor biologically relevant effects mediated by uPAR-del4/5 in human breast cancer and also ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, although several uPAR mRNA splice variants have been described, some being clearly associated to disease [14][15][16], no experimental analysis of their cellular properties was reported so far. The present study, combining in vitro and in vivo experimental approaches, clearly demonstrates tumor biologically relevant effects mediated by uPAR-del4/5 in human breast cancer and also ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several mRNA splice variants of uPAR have been identified and their expression analyzed in human cells and tissues [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we found that SR cells expressed two high molecular weight bands. Although additional bands are often suggested to be due to glycosylation, it has also been reported that uPAR exists in different isoforms, which can be either membranebound or secreted (24). This is of particular interest, as NFkB binds to the uPAR promoter (25) and MMP-2 and -9 can be activated by plasmin-activated uPAR-bound uPA (26), which has also been shown to play a role in glioblastoma invasion (27).…”
Section: Ikba Superrepressor-expressing Cells Do Not Efficiently Procmentioning
confidence: 99%
“…This is essential as uPAR exists in several soluble forms generated from both mRNA splicing and proteolytic cleavage (1). Did the authors measure the same suPAR species using the same monoclonal antibody as we did?…”
Section: Mateusz Siedlinskimentioning
confidence: 99%